Kearifan Lokal Masyarakat Desa Bakung dalam memanfaatkan Resam (Gleichenia linearis), Seduduk (Melastoma malabathricum) dan Tembesu (Fagraea fragrans) yang Tumbuh di Tanah Bergambut sebagai Obat Herbal - Oom Komalasari; Sri Maryani; Oktaf Juairiyah; Dian Novriadhy (Seminar Nasional Lahan Suboptimal, 2018)
Komalasari et al, 2019. Local Wisdom of Bakung People in Using Resam (Gleichenia linearis), Seduduk (Melastoma malabathricum) and Tembesu (Fagraea fragrans) grown in the Area of Peat Soil as Herbal Medicine. pp. 354-359.   Resam, Seduduk and Tembesu can be used as Herbal Medicine. Those plants grow most in the area of Sriwijaya botanical garden of South Sumatra Province in which its soil is peated. With their local wisdom, the people of Bakung village have been making use of resam, seduduk and tembesu as herbal medicine. The aim of this research was to identify secondary metabolites from resam, seduduk and tembesu which play a role so that they can be useful for drugs and to find out whether the efficacy of the three plant species has been scientifically proven (based on literature studies). The informants of the research were the people of Bakung village living surrounding Sriwijaya botanical garden. The data were colllected by well-structured interview, test of laboratorium, and literature studies. The data were analyzed using descriptive.analysis. The results revealed that the people living surrounding Sriwijaya botanical garden used resam for headache, seduduk leaves for diare, and tembesu leaves for itching. Each ethanol extract of leaves of tembesu, seduduk, and resam contain compound of flavonoid, alkaloid, steroid, saponin, tanin dan quinon. The local wisdom of  the Bakung Village community living around the Sriwijaya botanical garden in using seduduk leaves as a diarrhea drug has been scientifically proven, but for tembesu leaves as a cure for itching and resam as a headache  drug so far has been scientifically proven.